Pengaruh Literasi Digital dan Motivasi Berwirausaha Berbasis Gender terhadap Kinerja Reseller di UMKM Madu Hutan Dbee's Keca - Dewi Silvi Wulandari; Tuti Asmala (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The advancement of digital technology requires resellers to possess digital literacy skills and strong entrepreneurial motivation to enhance their business performance. However, there are still resellers who have not optimally utilized digital technology or developed a strong drive to grow their businesses. This study aims to analyze the impact of these two factors on reseller performance. This study employs a quantitative approach using descriptive and verificative methods. The research sample consists of 30 resellers, selected using the saturated sampling technique. Data collection was conducted via questionnaires using a Likert scale, while data analysis involved validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, partial testing (t-test), and simultaneous testing (F-test) using IBM SPSS Statistics 25. The research results indicate that digital literacy and gender-based entrepreneurial motivation influence reseller performance at the DBee's Forest Honey MSME in Parungponteng District, Tasikmalaya Regency. Thus, enhancing digital literacy and gender-based entrepreneurial motivation can support improved reseller performance at the DBee's Forest Honey MSME.